2020
DOI: 10.3389/fmicb.2019.02980
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Presence of Aspergillus Species and Mycobacterium Species in the Respiratory Tract of Patients: Underestimated Co-occurrence?

Abstract: Objectives: Aspergillus and Mycobacterium are opportunistic pathogens that can cause severe pulmonary diseases. To date, the clinical significance of their concomitant isolation and potential interactions in the lung remains poorly understood. The aim of this study was to assess the prevalence of their concomitant isolation from respiratory samples, and to depict the related clinical and microbiological characteristics. Methods: A retrospective monocentric study was conducted from January 2011 to December 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In one study, co-isolation of Aspergillus in respiratory samples of patients with confirmed M. tuberculosis was achieved in 50 out of 140 (35.7%) patients, of whom 92% had underlying lung conditions, 35 (70%) had positive Aspergillus IgG, and 3 (6%) were confirmed to have CPA [33]. Among HIV-TB co-infected Ugandans, 9% of the patients had a positive Aspergillus IgG at the end of their TB treatment [35].…”
Section: Can Ptb and Cpa Coexist?mentioning
confidence: 99%
“…In one study, co-isolation of Aspergillus in respiratory samples of patients with confirmed M. tuberculosis was achieved in 50 out of 140 (35.7%) patients, of whom 92% had underlying lung conditions, 35 (70%) had positive Aspergillus IgG, and 3 (6%) were confirmed to have CPA [33]. Among HIV-TB co-infected Ugandans, 9% of the patients had a positive Aspergillus IgG at the end of their TB treatment [35].…”
Section: Can Ptb and Cpa Coexist?mentioning
confidence: 99%
“…Person to person transmission has been suggested for M. abscessus but has not been fully demonstrated [68][69][70]. This ubiquity and exposure poses an enormous challenge for clinicians, since isolation of NTM from a clinical sample may only indicate a transient or persistent colonization, or an infection [71]. Aspergillus, Cryptococcus and Histoplasma, as typical environmental fungi, are not transmissible between humans.…”
Section: The Aetiological Agents: Ntm and Fungimentioning
confidence: 99%
“…the severity of the clinic manifestations being conditioned by the host immune status [93]. The existence of underlying pulmonary disease and immune disorders favor infections by both opportunistic pathogens fungi and NTM [71].…”
Section: The Human Host: Predisposing Conditions For Ntm Fungal Infementioning
confidence: 99%
See 2 more Smart Citations